Survival Analysis of Patients with Luminal and Non-Luminal Subtype Breast Cancer Receiving Vinorelbine Therapy at Sanglah General Hospital, Denpasar, Bali - Dewa Putu Satria Juristiasa; Putu Anda Tusta Adiputra; Dewa Made Sukrama (Indonesian Journal of Cancer, 2022)
Introduction: Breast cancer is the most common type and lethal cancer affecting women. Meanwhile, vinorelbine is one of the chemotherapy agents used for luminal and non-luminal breast cancer. Therefore, this study aims to determine the survival difference between patients with luminal and non-luminal subtype breast cancer treated with vinorelbine.Methods: This study was a retrospective cohort. Women with breast cancer treated with vinorelbine were classified based on estrogen receptor (ER), progesteron receptor (PR), human epidermal growth factor receptor-2 (HER-2) markers, and subtypes. The subjects were followed up to chemotherapy visits with vinorelbine recorded in the medical record. The survival analysis between subtypes was analyzed by the Kaplan-Meier curve.Results: : One hundred women were obtained with a mean age of 52.36 ± 10.45 years. Based on immunohistochemistry, 60% were ER-positive, 53% were PR positive, and 57% were HER-2- positive. Based on the subtype, 67% were luminal, while 33% were non-luminal. All subjects had a mean survival duration of 155.38 days (95% CI 128.05-182.71). The stratified survival analysis showed a significant difference in survival duration based on HER-2 marker and subtype. The subjects with HER-2 positive survived longer with a mean of 203.37 days (190.72–216.02) than those with HER-2 negative with a mean of 90.10 days (65.68-114.53) (p<0.001). In addition, the subjects with the luminal subtype survived longer with a mean of 174.84 (142.72-206.94) than those with non-luminal with a mean of 90.10 (65.68-114.53) (p = 0.04).Conclusion: There was a significant difference in survival duration between women with breast cancer treated with vinorelbine chemotherapy who were HER-2 positive, HER-2 negative, and luminal and non-luminal subtypes.